Protein-Protein Interaction Inhibitors Targeting the Eph-Ephrin System with a Focus on Amino Acid Conjugates of Bile Acids - Lorenzo Guidetti; Riccardo Castelli; Laura Scalvini; Francesca Ferlenghi; Miriam Corrado; Carmine Giorgio; Massimiliano Tognolini; Alessio Lodola (MDPI AG, 2022)
The role of the Eph-ephrin system in the etiology of pathological conditions has been consolidated throughout the years. In this context, approaches directed against this signaling system, intended to modulate its activity, can be strategic therapeutic opportunities. Currently, the most promising class of compounds able to interfere with the Eph receptor-ephrin protein interaction is composed of synthetic derivatives of bile acids. In the present review, we summarize the progresses achieved, in terms of chemical expansions and structure-activity relationships, both in the steroidal core and the terminal carboxylic acid group, along with the pharmacological characterization for the most promising Eph-ephrin antagonists in in vivo settings.